Theological Approach in Islamic Studies - Rifqi Muntaqo; Siswanto Siswanto (Institut Agama Islam Negeri (IAIN) Curup, 2016)
In the discourse of contemporary religious studies, the phenomenon of human religiosity can be viewed from any angle of approaches; one of the approaches is understanding religion which is named theological approach. There are two areas of religious studies, namely the teachings and religiosity. Teachings are the texts (oral or written) that are sacred and sources of reference for religious followers. For Islam, the texts are the Qur'an and Hadith. Religiosity is a behavior sourced directly or indirectly from the texts. The purpose of this paper is to understand Islam from its religious side with a theological approach. Theological approach is an approach to religious understanding that emphasizes the form of performance or religious symbols. There are several alternatives offered by theology experts, such as public post-theological, sociological approach, and normative theological approach. Keywords: theological approach, Islamic studies